1999
DOI: 10.1139/v99-113
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction and oxidation of DDT

Abstract: Electrolysis has been studied as a possible method to treat DDT wastes. In methanol, the major process was dehydrochlorination to DDE followed by further reduction. In an aqueous emulsion containing 1% heptane and 0.1% Triton SP-175®, DDT was reduced at a deposited lead electrode with sodium sulphate as the supporting electrolyte by sequential hydrodechlorination of the aliphatic chlorine atoms. An excellent material balance was achieved, but the current efficiency was poor, even at low current densities. Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This concentration effect was noticed some time ago in a study stating that the more significant application of electrochemical technology should not be anodic oxidation but the cathodic dechlorination of chlorinated pesticides. 165 Although this cathodic process is not a final treatment, a very significant decrease in the toxicity of chlorinated pesticides is obtained, and the cathodic process may be a good alternative when combined with cheaper treatments. 166,167 A final application of electrolytic systems is to modify the adsorption capacity 168 of an adsorbent or ion exchange processes 169 of a resine using electrochemically assisted processes.…”
Section: Anodic Oxidation and Cathodic Dechlorinationmentioning
confidence: 99%
“…This concentration effect was noticed some time ago in a study stating that the more significant application of electrochemical technology should not be anodic oxidation but the cathodic dechlorination of chlorinated pesticides. 165 Although this cathodic process is not a final treatment, a very significant decrease in the toxicity of chlorinated pesticides is obtained, and the cathodic process may be a good alternative when combined with cheaper treatments. 166,167 A final application of electrolytic systems is to modify the adsorption capacity 168 of an adsorbent or ion exchange processes 169 of a resine using electrochemically assisted processes.…”
Section: Anodic Oxidation and Cathodic Dechlorinationmentioning
confidence: 99%
“…Figure depicts structures of DDT and its various degradation products. Electrochemical research has involved the reduction of DDT at different electrodes and in various solvents. Depending on the choice of conditions, both partial and complete dechlorinations of DDT can be achieved to afford products such as DDD, 4,4′-(2,2-dichloro­ethene-1,1-diyl)­bis­(chlorobenzene) (DDE), 4,4′-(2-chloro­ethene-1,1-diyl)­bis­(chlorobenzene) (DDMU), and 4,4′-(ethene-1,1-diyl)­bis­(chlorobenzene) (DDNU). Moreover, the electrodegradation of DDT in an ionic liquid was examined …”
Section: Halogenated Environmental Pollutantsmentioning
confidence: 99%
“…Shown in Figure 3 are the structures of DDT and its degradation products. Subsequent investigations involved the reduction of DDT in a variety of solvent systems and at a variety of electrodes (including mercury, lead, nickel, and graphite felt) [52][53][54][55][56]; this work demonstrated that, depending on the choice of experimental conditions, different degrees of dechlorination could be achieved to produce DDD, DDE, DDMU, and DDNU [52][53][54][55][56]. In addition, ionic liquids have been employed as media for the electrochemical degradation of DDT [57].…”
Section: Halogenated Organic Pesticidesmentioning
confidence: 99%